Review of the genus Myrmozercon Berlese (Acari: Laelapidae), with description of a new species from Iran - Joharchi, Omid; Babaeian, Esmaeil; Seeman, Owen D. (Zootaxa, 2015)
A new species of laelapid mite, Myrmozercon hunteri sp. nov. associated with Myrmica sp. (Hymenoptera: Formicidae), is described and illustrated. A key to 18 species of Myrmozercon is presented. Ten further species, all described prior to 1950, are briefly diagnosed but cannot be included in the key. Myrmozercon is shown to include a distinct group, Myrmozercon sensu stricto, which all have short, highly hypotrichous legs and a series of other consistent character states. This group probably arises from within Myrmozercon sensu lato, which have long legs with little or no hypotrichy, but some species also have character states found in Myrmozercon s.s. Myrmozercon ovatum Karawajew, 1909 is regarded a junior synonym of M. brevipes Berlese, 1902.